2023
DOI: 10.1039/d2fo03308a
|View full text |Cite
|
Sign up to set email alerts
|

Platycodin D ameliorates hyperglycaemia and liver metabolic disturbance in HFD/STZ-induced type 2 diabetic mice

Abstract: In this work, we investigated the ameliorative effects of platycodin D (PD), a major active chemical ingredient isolated from the roots of Platycodon grandiflorum (PG), on a high-fat diet (HFD)/streptozotocin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
(64 reference statements)
2
13
0
Order By: Relevance
“…An early report indicated that PD inhibits Aβ-induced oxidative stress and inflammatory responses in BV-2 cells by modulating the TLR4/NF-κB (p65) and Nrf2/HO-1 signaling pathways . Moreover, PD could protect mice from hippocampal ischemia/reperfusion injury by increasing antioxidant enzymes . Our previous work demonstrated that PD not only ameliorated diabetic nephropathy and liver disease , but also ameliorated Alcl 3 +D-gal-induced neuronal apoptosis and cognitive dysfunction via activating AMPK activity .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…An early report indicated that PD inhibits Aβ-induced oxidative stress and inflammatory responses in BV-2 cells by modulating the TLR4/NF-κB (p65) and Nrf2/HO-1 signaling pathways . Moreover, PD could protect mice from hippocampal ischemia/reperfusion injury by increasing antioxidant enzymes . Our previous work demonstrated that PD not only ameliorated diabetic nephropathy and liver disease , but also ameliorated Alcl 3 +D-gal-induced neuronal apoptosis and cognitive dysfunction via activating AMPK activity .…”
Section: Introductionmentioning
confidence: 90%
“…Fasting blood glucose (FBG) levels were measured at days 7, 14, 21, and 28 after STZ injection using blood taken from the tail vein using an ACCU-CHEK Performa FBG monitor. Mice with stable FBG values in the range of 7.8–16.67 mmol/L were selected for the study. , After 13 weeks of dietary manipulation with a high-fat and high-sugar regimen, the T2DM mice were randomly assigned to three groups: (1) normal group (mice received 0.5% CMC-Na, n = 10); (2) model group, (mice received HFD + STZ at 100 mg/kg, n = 10); and (3) HFD + STZ + PD (2.5 mg/kg, n = 10) . The optimal dose of PD was determined based on the results of previous pre-experiments by the subject group.…”
Section: Methodsmentioning
confidence: 99%
“…PD (purity, ≥98%) was isolated from the aerial parts of P. grandiflorum and extracted by our research group. 25 Streptozocin (STZ) and wheat germ agglutinin (WGA) were purchased from Solarbio (Beijing, China). The high-fat diet (HFD) comprised 60% of total kilocalories based on D12492 (Beijing Hua Fukang guidelines).…”
Section: Methodsmentioning
confidence: 99%
“…The mice were randomly assigned to three groups (n = 8): a normal group, a diabetes group, and a PD group (2.5 mg/kg). 25 All experimental animals underwent adaptive feeding for 7 days prior to the induction of diabetes in mice. After 8 weeks of HFD feeding combined with STZ (100 mg/kg) dissolved in preprepared citrate buffer (pH = 4.2−4.4) in an ice bath, a single dose of STZ was intraperitoneally injected into mice to induce diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PD may have a potential direct effect on AMPK and other key glycolipid metabolism proteins. To summarize, PD modulation of hepatic glycolipid metabolism abnormalities is promising for T2D therapy in the future ( Shen et al, 2023 ). Diabetes mellitus is a group of physiological dysfunctions associated with hyperglycemia-mediated oxidative stress and apoptosis in pancreatic β-cells.…”
Section: Pharmacology Of Pldmentioning
confidence: 99%